A efetividade ao direito fundamental ao meio ambiente ecologicamente equilibrado : das licitações sustentáveis na aplicabilidade do performance bond - Checcucci, Gustavo Leite Caribé (2017)
The present work intends to analyze the extent to which the practice of sustainable biddings, using performance bond, seeks to collaborate with the fundamental right to the environment and bring legal certainty to the parties. The bibliographic research was used from the doctrinal analysis relevant to the theme, specially the branches of environmental, Administrative and Constitutional Law, as well the documentary research, besides the analysis of legal texts and both foreign and homeland jurisprudence. Furthermore, it has utilized the dialectical method so that the jurisprudential and doctrinal counterpoints could provide larger legal-philosophical foundation to the research. As a result, it was verified that the environmental balance is a duty for the Public Administration, as it is for the society and the instrument proposed in this research – by means of environmental regulation through the sustainable public biddings – will be able to cooperate with the search of sustainable development, consolidated by the performance bond. It is concluded that this will bring legal certainty to the administrative contract hereby tendered, finish the public work in a sustainable way, as well as to the environment, due to the requirements required by the insurer, which becomes responsible for the faithful fulfillment of the contract in its completeness, generating benefits to the environment, the public treasury, as well as to present and future generations.